2023
DOI: 10.1162/netn_a_00263
|View full text |Cite
|
Sign up to set email alerts
|

Stability and dynamics of a spectral graph model of brain oscillations

Abstract: We explore the stability and dynamic properties of a hierarchical, linearized, and analytic spectral graph model for neural oscillations that integrates the structuring wiring of the brain. Previously we have shown that this model can accurately capture the frequency spectra and the spatial patterns of the alpha and beta frequency bands obtained from magnetoencephalography recordings without regionally varying parameters. Here, we show that this macroscopic model based on long-range excitatory connections exhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 94 publications
(134 reference statements)
0
23
0
Order By: Relevance
“…We compare the performance of SBI-SGM with the performance of the annealing SGM approach [39][40][41],…”
Section: Implementation Detailsmentioning
confidence: 99%
“…We compare the performance of SBI-SGM with the performance of the annealing SGM approach [39][40][41],…”
Section: Implementation Detailsmentioning
confidence: 99%
“…The model used here is similar to the SGM developed previously [25,26,66,67], and is described in detail in the supplementary document. Briefly, it is characterized by the following model parameters at the mesoscopic level: excitatory time constant (τ e ), inhibitory time constant (τ i ), excitatory gain (g ee , assumed to be 1 for parameter identifiability), inhibitory gain (g ii ), coupled population gain (g ei ); and the following model parameters at the macroscopic level: coupling constant (α), speed (v), graph excitatory time constant (τ G ).…”
Section: Modelmentioning
confidence: 99%
“…Parameter initial guesses and bounds for estimating the static spectra are specified in Table 1. We defined three different bounds on the neural gain terms to ensure that the model is stable, based on prior work on model stability [66]. First, we supplied a larger bound on the neural gains for optimization.…”
Section: Model Parameter Estimationmentioning
confidence: 99%
“…The structure of SGM is similar to that of Jansen-Rit model (Jansen and Rit, 1995 ; Sanz-Leon et al, 2015 ). Further methodological comparisons can be found elsewhere (Verma et al, 2022b ).…”
Section: Recent Advances In Structure-function Modelsmentioning
confidence: 99%
“…Since the development of the SGM, there have been various extensions as well. We recently improved SGM by enhancing the biophysical interpretability of the mesoscopic model (Verma et al, 2022a ), and subsequently demonstrated various stability properties of this improved model (Verma et al, 2022b ). In the latter, we also outlined a strategy to capture temporal fluctuations in MEG by fitting the SGM parameters to MEG frequency spectra at various time points.…”
Section: Recent Advances In Structure-function Modelsmentioning
confidence: 99%